Морфофункциональные особенности апикальных структур хоботка кровососущих комаров (Culicidae) - Пучкова, Л.В. (Вестник зоологии, 1977)
Mosquito labella are three-jointed. Exoskeleton of the first joint is rudimentary. but, as well as the progressively developed endoskeleton of this joint, ensures a support-motor function and realizes articulation of labella with labium and ligule. The second joint fulfils mainly the support function, the third one fulfils besides the sensory function two additional functions: participation in delivery of free liquids to food-taking opening of the snout and creation of sticking effect for retaining style, piercing the skin of an object of feeding, in a beam. The third joint is non-uniformly long and sclerotized along the outer and inner surface. Its form is not constant depending on the degree of turgorization and position of the support lamella, derivatives of the endoskeleton of the first joint. In total the terminal appendages of the snout, including ligula, are arranged in mosquito of the genera Culiseta, Culex, Aedes and Anopheles in the morphological series correlating with some peculiarities of their ecology.